Identification of risk factors for the progression of age-related macular degeneration: a systematic review and meta-analysis of cohort studies - Tian, Moqi; Zhang, Baike (Frontiers in Medicine, 2025)
BackgroundAge-related macular degeneration (AMD) is a retinal degenerative disease that primarily affects the elderly population and is a leading cause of vision loss in older adults. There is a lack of research comprehensively examining the risk factors for AMD progression. This study aimed to identify the risk factors influencing the development of AMD using a meta-analysis approach.MethodsWe systematically searched the PubMed, Embase, and Cochrane Library databases from their inception until November 2024. Summary effect estimates were assigned as odds ratios (ORs) with 95% confidence intervals (CIs) using a random effects model. Further exploratory analyses included sensitivity and sub-group analyses.ResultsEighteen cohort studies involving 38,697 individuals were included in the final meta-analysis. We noted male versus female was associated with a reduced risk of AMD (OR: 0.84; 95% CI: 0.72–0.98; p = 0.027). The identified risk factors for AMD included per 5-year increment in age (OR: 1.14; 95% CI: 1.09–1.19; p < 0.001), current smoking (OR: 1.28; 95% CI: 1.07–1.52; p = 0.007), alcohol intake (OR: 1.30; 95% CI: 1.00–1.67; p = 0.046), per 1 mmol/L increment in high-density lipoprotein (OR: 1.21; 95% CI: 1.08–1.36; p = 0.001), total drusen >10% of the grid (OR: 7.85; 95% CI: 4.66–13.23; p < 0.001), presence of depigmentation (OR: 6.39; 95% CI: 2.48–16.44; p < 0.001), presence of hyperpigmentation (OR: 6.03; 95% CI: 1.94–18.73; p = 0.002), and >10 small drusen (OR: 7.21; 95% CI: 2.10–24.72; p = 0.002).ConclusionThis study systematically identified the risk factors for AMD progression, and exploratory analyses were performed to determine the risk factors for early and late AMD. Patients at high risk of AMD should be monitored to improve modifiable risk factors and slow the progression of AMD.Systematic review registrationINPLASY platform (INPLASY2024120036).